Lord Lancaster courts a scandal - Dickson, Helen (Harlequin historicals., 2023)
"Tasked with escorting Miss Anna Harris from India back home to England, Lord William Lancaster doesn't expect his late best friend's sister to be so headstrong and determined--or so desirable! But their attraction can go no further, for William is bound by duty to wed, and Anna's scandalous background and desire for independence are unsuitable for the future Marchioness of Elvington."--Back cover.